Peran Kepemimpinan Kepala Madrasah dalam Implementasi Manajemen Berbasis Madrasah untuk Meningkatkan Mutu Pendidikan Islam - Uchik Rini Qomaria; Muhammad Husni (CV. Lentera Literasi Indonesia, 2026)
This study aims to analyze the role of madrasa principal leadership in the implementation of School-Based Management (SBM) as an effort to improve the quality of Islamic education. This study employed a qualitative approach using a library research method. The data were obtained through the examination of various literature sources, including books, scientific journals, articles, and documents relevant to the research topic. The data analysis technique used was content analysis to gain an in-depth understanding of the concept of madrasa principal leadership and the implementation of SBM in Islamic education. The results of the study indicate that the implementation of School-Based Management provides autonomy for madrasas in managing educational resources independently, participatively, and with an orientation toward improving educational quality. The success of SBM implementation is greatly influenced by the leadership of the madrasa principal as a leader, motivator, supervisor, and decision-maker in mobilizing all educational components. In addition, improving the quality of Islamic education is carried out through strengthening the quality of learning, enhancing teacher professionalism, developing a religious culture, and conducting continuous evaluation. Madrasa principal leadership based on Islamic values such as trustworthiness (amanah), consultation (syura), justice, responsibility, and exemplary behavior is able to create effective madrasa governance and support the comprehensive and sustainable improvement of the quality of Islamic education.